Writing Interventions for Students With Intellectual and Developmental Disabilities: A Meta-Analysis. (June 2023) - Rodgers, Derek B.; Loveall, Susan J.
Students with intellectual and developmental disabilities (IDD) are likely to experience writing challenges that can negatively impact their overall academic, vocational, and social success. The goals of this study were to determine what writing interventions have been used with students with IDD, how their writing skills have been measured, the effects of those interventions, and study-level moderators via meta-analytic procedures. We identified 96 writing-related outcomes reported in 52 studies that included 424 students with IDD. A majority of studies used strategy instruction/self-regulated strategy development (SRSD), direct instruction, or response prompting to instruct writing skills, and the most common outcome measures were related to writing output, conventions, quality rubrics, elements, and spelling. Results indicated that writing interventions led to significant improvements in students' writing skills. These effects were moderated by intervention type and study quality.